Description of a new species of the genus Paecilocaulus Fairmaire (Coleoptera: Anthribidae) from Fiji - Trýzna, Miloš; Blažej, Lukáš (Zootaxa, 2017)
The new species Paecilocaulus inexpectatus Trýzna sp. nov. (Anthribidae: Anthribinae: Xenocerini) from Fiji is described. Male genitalia are illustrated and colour photographs of P. inexpectatus and P. picturatus Fairmaire, 1881 are provided.